The making of Pakistani human bombs - Iqbal, Khuram (Lexington Books, 2015)
Based on interviews with failed suicide bombers, officials of Pakistani law enforcement agencies involved in interrogating high-profile self-immolation attacks, and content analysis of Jihadi publications produced in local languages, this book offers the first empirically grounded analysis of suicide terrorism in Pakistan.